Qualidade de frutos de mangabeira de diferentes estágios de maturação tratados com CaCl2 (Research, Society and Development, 2021)
Hancornia speciosa is a fruit tree, popularly known as mangabeiras. The mangaba, fruits of this tree, are quite appreciated for their organoleptic characteristics. Because it is a climacteric fruit, this fruit has very high perishability. The use of products that extend the useful life is necessary. Calcium chloride (CaCl2) has been shown to be an alternative in post-harvest because it promotes few changes in fruit quality and increases the storage period. Thus, the objective of this work was to evaluate quality attributes of mangaba fruits in two stages of maturation, 'Immature' and 'Mature', submitted to CaCl2 application, in four storage times (0, 2, 4 and 6 days) under ambient atmosphere. During the experiment, the loss of fresh weight, color, pH, titratable acidity, soluble solids and SS/TA ratio were evaluated. It was verified that the 'mature' fruits showed a higher acidity and soluble solids content, even with the application of CaCl2, the difference that the loss with the application of CaCl2 was smaller. Unlike '‘Immature’ and ‘Immature’ fruits with CaCl2 in which these characteristics were acquired as the experiment was conducted, in addition to presenting lower values for weight loss, pH and color.